Nickel-coated aluminum / graphene composite aerogel material and preparation method thereof

CN120483126BActive Publication Date: 2026-10-09NINGBO GRAPHENE INNOVATION CENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510368091.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2026-10-09
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

[0006]为了克服上述缺陷,现有技术有采用钛酸钡这种无机物物与石墨烯气凝胶复合制备吸波材料,钛酸钡具有高介电常数和低介电损耗,制备的吸波材料具有一定的吸波性能的改善,但是这类材料其复合反射损耗最低仅为-28.53dB,对应的有效吸收频段相对较窄,吸波性能仍然不是很理想

Benefits of technology

[0026]1. This application employs a nickel-clad aluminum composite with graphene oxide. The nickel in the nickel-clad aluminum composite provides magnetic loss performance to enhance the overall microwave loss capability, while the aluminum in the nickel-clad aluminum composite provides dielectric loss capability. Therefore, the choice of nickel-clad aluminum in this application can improve the magnetic and dielectric loss capabilities of the graphene aerogel composite microwave absorbing material. The lowest reflection loss of the existing barium titanate and graphene aerogel composite is only -28.53dB, while the lowest reflection loss of the nickel-clad aluminum and graphene oxide aerogel composite in this application is -56.1638dB. Therefore, the microwave absorption performance of the microwave absorbing agent prepared by this formulation is significantly improved, and the effective absorption frequency band it can cover is also wider.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120483126B_ABST
    Figure CN120483126B_ABST
Patent Text Reader

Abstract

The application discloses a kind of nickel-coated aluminum / graphene composite aerogel materials and preparation method thereof, and the preparation raw materials of the material include: nickel-coated aluminum, graphene oxide, wherein the mass ratio of the nickel-coated aluminum and the graphene oxide is 0.06-0.18:1, and the nickel-coated aluminum and the graphene oxide are reduced by a reducing agent to obtain the final aerogel material.The technical scheme of the application has the advantages of improving the magnetic loss capability of graphene aerogel composite wave-absorbing material and the dielectric loss capability, greatly improving the wave-absorbing performance, and covering a wider effective absorption frequency band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of composite materials containing graphene oxide, and more particularly to a nickel-coated aluminum / graphene composite aerogel material and its preparation method. Background Technology

[0002] Graphene is a two-dimensional carbon nanostructure material with a stable structure, low density, high specific surface area and excellent conductivity. Its layered structure can enhance electromagnetic interaction, thereby achieving strong conductivity and polarization loss, and has the potential to become a high-quality microwave absorbing material.

[0003] However, the practical application of graphene-based microwave absorbing materials is limited due to their poor impedance matching.

[0004] Graphene possesses excellent electrical and thermal conductivity, good durability, and manipulation, making it a potential high-quality microwave absorbing material. Compared to two-dimensional graphene materials, the three-dimensional porous structure of graphene aerogels can generate a lower relative complex permittivity and provide more free space within the material, improving impedance matching between graphene and free space and significantly enhancing multiple reflections and scattering of incident electromagnetic waves. Furthermore, the complex conductive network and high porosity of graphene aerogels help prevent graphene aggregation, accelerate the expansion of electron conduction paths and charge transfer, thereby promoting the conversion of electromagnetic wave energy into heat. Simultaneously, when electromagnetic waves enter graphene aerogels, the high porosity extends the transmission path, and the energy is dissipated after multiple reflections and scattering. More importantly, the complexity of the internal conductive pathways of graphene aerogels gives them a stronger electromagnetic response to electromagnetic waves over a wider frequency range.

[0005] However, graphene is non-magnetic, resulting in very weak magnetic loss in graphene aerogels and poor impedance matching, which hinders their practical application. Therefore, introducing magnetic materials, such as magnetic metals and alloys, and magnetic metal oxides, into graphene aerogels can optimize impedance matching conditions and further improve microwave absorption performance.

[0006] To overcome the above-mentioned defects, existing technologies have used barium titanate, an inorganic material, to combine with graphene aerogel to prepare microwave absorbing materials. Barium titanate has a high dielectric constant and low dielectric loss, and the prepared microwave absorbing materials have certain improvements in microwave absorption performance. However, the composite reflection loss of such materials is as low as -28.53dB, and the corresponding effective absorption frequency band is relatively narrow, so the microwave absorption performance is still not ideal.

[0007] In addition, there are existing technologies for preparing microwave absorbing materials by combining ferromagnetic materials with graphene oxide. While ferromagnetic materials can construct heterogeneous interfaces to enhance interfacial polarization loss and improve the impedance matching performance of graphene-based materials, and the magnetic loss properties of ferromagnetic materials themselves can further enhance the magnetic loss capability of composite materials, the current methods mostly involve combining single-element metal materials or modified single-element metal materials with graphene oxide to prepare microwave absorbing materials. However, there are few reports on the use of metal alloy materials for preparing microwave absorbing materials. How to effectively screen such alloy materials and graphene oxide to prepare a new type of microwave absorbing material that can give full play to the overall advantages of the alloy material while taking into account the properties of each individual metal element in the alloy material, so as to achieve synergy and provide both magnetic loss capability and dielectric loss capability of the microwave absorbing material, has become one of the technical problems to be solved in this field. Summary of the Invention

[0008] This application addresses the aforementioned shortcomings of the prior art by providing a nickel-clad aluminum / graphene composite aerogel material that can improve both the magnetic loss capability and dielectric loss capability of graphene aerogel composite microwave absorbing materials, thereby significantly enhancing their microwave absorption performance and enabling them to cover a wider effective absorption frequency band.

[0009] To solve the above-mentioned technical problems, the technical solution adopted in this application is: a nickel-coated aluminum / graphene composite aerogel material, the raw materials for preparing the material include: nickel-coated aluminum and graphene oxide, wherein the mass ratio of nickel-coated aluminum to graphene oxide is 0.06 to 0.18:1, and the nickel-coated aluminum and graphene oxide undergo a reduction reaction with a reducing agent to obtain the final aerogel material.

[0010] Furthermore, the graphene oxide has a sheet diameter of 0.4–5 μm and a thickness of 0.5–1.0 nm.

[0011] Furthermore, the nickel-clad aluminum is composed of a layer of nickel wrapped around an aluminum core, with a composition of 60-90 wt% nickel and 10-40 wt% aluminum.

[0012] Furthermore, the nickel-clad aluminum is composed of a layer of nickel wrapped around an aluminum core, with a composition of 70-85 wt% nickel and 15-25 wt% aluminum.

[0013] Furthermore, the reducing agent is L-ascorbic acid.

[0014] Furthermore, the combined mass ratio of the reducing agent to the graphene oxide and the nickel-coated aluminum is 1:0.5-1.5.

[0015] This application also provides a method for preparing the above-mentioned nickel-coated aluminum / graphene composite aerogel material, the specific steps of which include:

[0016] (1) Preparation of graphene oxide aqueous dispersion: Weigh graphene oxide powder and add it to deionized water, mix it with ultrasound at room temperature, adjust the pH of the mixture to neutral, and then mechanically peel it off by a high-speed disperser to obtain graphene oxide aqueous dispersion.

[0017] (2) Preparation of nickel-coated aluminum / graphene composite aerogel material: Add nickel-coated aluminum to the aqueous dispersion of graphene oxide prepared in step (1) and sonicate at room temperature to fully disperse the nickel-coated aluminum in the aqueous dispersion of graphene oxide. Then add the reducing agent L-ascorbic acid. Then seal the reaction vessel and transfer it to a constant temperature chamber. Keep it at 80-100℃ for 1-5 hours. Then cool it to room temperature and use liquid nitrogen to quickly freeze the obtained aerogel block. Then transfer it to a freeze dryer and freeze dry for 24-96 hours to obtain the nickel-coated aluminum / graphene composite aerogel material.

[0018] Furthermore, in step (1), the concentration of the graphene oxide powder in the dispersion ranges from 0.01 to 0.02 g / mL.

[0019] Furthermore, the mass ratio of nickel-coated aluminum to graphene oxide in step (2) is 0.06 to 0.18:1.

[0020] Furthermore, the mass ratio of the reducing agent, graphene oxide, and nickel-coated aluminum in step (2) is 1:0.5-1.5.

[0021] Furthermore, the mass ratio of the reducing agent described in step (2) to the sum of the masses of graphene oxide and nickel-coated aluminum is 1:0.8-1.2.

[0022] Furthermore, in step (2), the temperature of the transfer to the constant temperature chamber is 85-95℃ and maintained for 2.5-3.5 hours.

[0023] Furthermore, the quick-freezing described in step (2) is done by using liquid nitrogen. The specific operation process is to place the sample in a low-temperature resistant container, then add liquid nitrogen, and after a period of time (about 1 minute), the sample is quickly frozen into a block. Because liquid nitrogen can quickly cool the sample to -196°C, the quick-freezing effect is achieved.

[0024] Furthermore, the freeze-drying temperature in step (2) is -55 to -60°C.

[0025] The advantages and beneficial effects of this application are as follows:

[0026] 1. This application employs a nickel-clad aluminum composite with graphene oxide. The nickel in the nickel-clad aluminum composite provides magnetic loss performance to enhance the overall microwave loss capability, while the aluminum in the nickel-clad aluminum composite provides dielectric loss capability. Therefore, the choice of nickel-clad aluminum in this application can improve the magnetic and dielectric loss capabilities of the graphene aerogel composite microwave absorbing material. The lowest reflection loss of the existing barium titanate and graphene aerogel composite is only -28.53dB, while the lowest reflection loss of the nickel-clad aluminum and graphene oxide aerogel composite in this application is -56.1638dB. Therefore, the microwave absorption performance of the microwave absorbing agent prepared by this formulation is significantly improved, and the effective absorption frequency band it can cover is also wider.

[0027] 2. In addition, this application also uses L-ascorbic acid as a reducing agent in the raw materials of the microwave absorbing agent. The use of this reducing agent can perform thermal reduction treatment on the surface of graphene oxide, so that its layers can "self-assemble" to form a three-dimensional network structure. This structure causes multiple reflections and scattering of incident electromagnetic waves, increases the transmission path of electromagnetic waves, and can also form a conductive network, thereby accelerating the effective migration of electrons.

[0028] 3. The nickel-clad aluminum alloy used in this application combines the properties of both nickel and aluminum. As a specific alloy structure, nickel-clad aluminum possesses low density, good electrical conductivity and magnetism, excellent microwave absorption performance, and corrosion resistance. It combines the magnetic loss of nickel with the electrical loss of aluminum, and also exhibits interfacial polarization loss between the nickel and aluminum phases. Therefore, nickel-clad aluminum has a wider absorption bandwidth and higher absorption efficiency. Furthermore, the core-shell structure of nickel-clad aluminum can prevent aluminum oxidation and corrosion, thus improving the service life of the absorbing agent. In contrast, elemental nickel and elemental aluminum, due to their significant density difference, are not easily uniformly dispersed in graphene oxide solution. Mixing them with graphene oxide to prepare aerogels results in poor synergistic effects among the three. Therefore, the specific nickel-clad aluminum alloy structure of this application is more conducive to the preparation of microwave absorbing materials.

[0029] 4. The preparation method of this application, wherein through the thermal reduction process, defects and residual functional groups on the graphene sheets will act as polarization centers, resulting in an imbalance in charge distribution, thereby forming dipole polarization and promoting the attenuation of electromagnetic waves.

[0030] 5. The preparation method of this application uses L-ascorbic acid to prepare a three-dimensional graphene aerogel through a thermal reduction process, which is fundamentally different from the treatment of graphene oxide by spray drying. After treatment of graphene oxide by spray drying, the graphene oxide remains a sheet structure rather than a three-dimensional structure. Therefore, the thermal reduction of this application causes the graphene oxide sheets to "self-assemble" with each other to form a three-dimensional network structure. This structure causes multiple reflections and scattering of incident electromagnetic waves, increasing the transmission path of electromagnetic waves. At the same time, it can also form a conductive network, thereby accelerating the effective migration of electrons. In addition, the subsequent quick-freezing process of this application can maintain the three-dimensional structure of the graphene hydrogel. The freeze-drying process sublimates and dries the ice to obtain the graphene aerogel structure.

[0031] 6. The preparation method of this application enables the graphene oxide sheets to "self-assemble" with each other to form a three-dimensional network structure. Then, nickel-coated aluminum can be relatively uniformly dispersed in this three-dimensional graphene aerogel structure, which is conducive to improving the synergistic effect between nickel-coated aluminum and graphene oxide, so as to obtain a high-performance microwave absorbing material. Attached Figure Description

[0032] Figure 1 The reflection loss curves of the nickel-coated aluminum / graphene composite aerogel material prepared in Example 1 at different thicknesses in the frequency range of 0.045 to 18 GHz.

[0033] Figure 2 The reflection loss curves of the pure graphene aerogel material prepared for Comparative Example 1 at different thicknesses in the frequency range of 0.045–18 GHz.

[0034] Figure 3 The graph shows the reflection loss curves of the nickel-coated aluminum / graphene composite aerogel material prepared in Example 2 at different thicknesses within the frequency range of 0.045–18 GHz.

[0035] Figure 4 The image shows the microstructure of the nickel-coated aluminum / graphene composite aerogel material prepared in Example 2.

[0036] Figure 5 The graph shows the reflection loss curves of the nickel-coated aluminum / graphene composite aerogel material prepared in Example 3 at different thicknesses within the frequency range of 0.045–18 GHz.

[0037] Figure 6 The reflection loss curves of the nickel / graphene composite aerogel material prepared for Comparative Example 2 at different thicknesses in the frequency range of 2–18 GHz are shown.

[0038] Figure 7 The reflection loss curves of the aluminum / graphene composite aerogel material prepared for Comparative Example 3 at different thicknesses in the frequency range of 2–18 GHz are shown. Detailed Implementation

[0039] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are merely preferred embodiments, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0040] Example 1:

[0041] A nickel-coated aluminum / graphene composite aerogel material and its preparation method are disclosed, with the specific implementation steps as follows:

[0042] (1) Preparation of graphene oxide aqueous dispersion: Weigh 0.5g of graphene oxide powder and add it to 50mL of deionized water. Sonicate at room temperature for a period of time until GO is completely dissolved. Adjust the pH to neutral and mechanically peel it off using a high-speed disperser to obtain the graphene oxide aqueous dispersion.

[0043] (2) Preparation of nickel-coated aluminum / graphene composite aerogel material: In step (1), 30 mg of nickel-coated aluminum (the nickel-coated aluminum powder is a commercially available product, which is composed of a layer of nickel wrapped around an aluminum core. In this example, the composition of the nickel-coated aluminum is 80 wt% nickel and 20 wt% aluminum) is added to the aqueous dispersion of graphene oxide. The mixture is then sonicated at room temperature for 30 min to ensure that the nickel-coated aluminum is fully dispersed in the aqueous dispersion of graphene oxide. Then, L-ascorbic acid, a reducing agent, is added in a mass ratio of 1:1 with the microwave absorber (graphene oxide and nickel-coated aluminum). The reaction vessel is then sealed and transferred to a constant temperature oven and kept at 90°C. After cooling to room temperature for 3 hours, the obtained aerogel block was rapidly frozen using liquid nitrogen (the specific operation process is to place the sample in a low-temperature resistant container, and then add liquid nitrogen for about 1 minute, and the sample is rapidly frozen into a block; because liquid nitrogen can quickly cool the sample to -196℃, the rapid freezing effect is achieved; the rapid freezing process is to maintain the three-dimensional structure of the graphene hydrogel, and the freeze-drying process sublimates and dries the ice to obtain the graphene aerogel structure). Then it was transferred to a freeze dryer, and the freeze-drying temperature was -55~-60℃ for 48 hours to obtain the nickel-coated aluminum / graphene composite aerogel material.

[0044] The nickel-coated aluminum / graphene composite aerogel material prepared in Example 1 was added to molten paraffin and molded into cylinders and cylinders.

[0045] Figure 1The graph shows the reflection loss curves of the nickel-clad aluminum / graphene composite aerogel material prepared in Example 1 at different thicknesses within the frequency range of 0.045–18 GHz. At a frequency of 13.96 GHz, the reflection loss reaches a minimum of -35.1393 dB across the entire frequency band, with a matching thickness of only 2.3 mm and an effective absorption bandwidth of 6.0149 GHz, essentially covering the entire Ku-band. This demonstrates that the nickel-clad aluminum / graphene composite aerogel absorbing material prepared in this method possesses excellent microwave absorption performance, achieving high-frequency microwave absorption even with a low matching thickness.

[0046] Example 2:

[0047] A nickel-coated aluminum / graphene composite aerogel material and its preparation method are disclosed, with the specific implementation steps as follows:

[0048] (1) Preparation of graphene oxide aqueous dispersion: Weigh 0.5g of graphene oxide powder and add it to 60mL of deionized water. Sonicate at room temperature for a period of time until GO is completely dissolved. Adjust the pH to neutral and mechanically exfoliate it through a high-speed disperser to obtain the graphene oxide aqueous dispersion.

[0049] (2) Preparation of nickel-coated aluminum / graphene composite aerogel material: In step (1), 60 mg of nickel-coated aluminum was added to the aqueous dispersion of graphene oxide and sonicated at room temperature for 30 min to ensure that the nickel-coated aluminum was fully dispersed in the aqueous dispersion of graphene oxide. Then, L-ascorbic acid, a reducing agent with a mass ratio of 1:1 with the microwave absorber (graphene oxide and nickel-coated aluminum), was added. The reaction vessel was then sealed and transferred to a constant temperature chamber. The chamber was kept at 95°C for 2.5 h. After cooling to room temperature, the resulting aerogel block was rapidly frozen using liquid nitrogen. (The specific operation process is to place the sample in a low-temperature resistant container, and then add liquid nitrogen for about 1 minute, and the sample will be quickly frozen into a block; because liquid nitrogen can quickly cool the sample to -196℃, the quick-freezing effect is achieved; the quick-freezing process is to maintain the three-dimensional structure of the graphene hydrogel, and the freeze-drying process sublimates the ice to obtain the graphene aerogel structure), and then transfer it to a freeze dryer. The freeze-drying temperature is -55~-60℃, and the freeze-drying time is 50h, which yields the nickel-coated aluminum / graphene composite aerogel material.

[0050] The nickel-coated aluminum / graphene composite aerogel material prepared in Example 2 was added to molten paraffin and molded into cylinders and cylindrical rings, which were used for electromagnetic parameter testing and microwave absorption (MA) measurement, respectively.

[0051] Figure 3The graph shows the reflection loss curves of the nickel-clad aluminum / graphene composite aerogel material prepared in Example 2 at different thicknesses within the frequency range of 0.045–18 GHz. At a frequency of 12.61 GHz, the reflection loss reaches a minimum of -56.1638 dB across the entire frequency band, with a matching thickness of only 2.5 mm and an effective absorption bandwidth of 5.5661 GHz. As the nickel-clad aluminum ratio increases, the reflection loss increases from -35.1393 dB to -56.1638 dB, demonstrating the beneficial effect of the nickel-clad aluminum alloy in increasing the carrier concentration of the graphene-based absorbing material on enhancing the dielectric loss performance of the nickel-clad aluminum / graphene composite aerogel absorbing material. This further confirms the feasibility of this approach.

[0052] Figure 4 The image shows the microstructure of the nickel-coated aluminum / graphene composite aerogel material prepared in Example 2. As can be seen from the image, in the nickel-coated aluminum / graphene composite aerogel material prepared by this method, the nickel-coated aluminum can be relatively uniformly dispersed in the aerogel structure, which is beneficial to improving the synergistic effect among the three components and thus obtaining a high-performance microwave absorbing material.

[0053] Example 3:

[0054] A nickel-coated aluminum / graphene composite aerogel material and its preparation method are disclosed, with the specific implementation steps as follows:

[0055] (1) Preparation of graphene oxide aqueous dispersion: Weigh 0.5g of graphene oxide powder and add it to 45mL of deionized water. Sonicate at room temperature for a period of time until GO is completely dissolved. Adjust the pH to neutral and mechanically exfoliate it through a high-speed disperser to obtain the graphene oxide aqueous dispersion.

[0056] (2) Preparation of nickel-coated aluminum / graphene composite aerogel material: In step (1), 90 mg of nickel-coated aluminum was added to the aqueous dispersion of graphene oxide and sonicated at room temperature for 30 min to ensure that the nickel-coated aluminum was fully dispersed in the aqueous dispersion of graphene oxide. Then, L-ascorbic acid, a reducing agent with a mass ratio of 1:1 with the microwave absorber (graphene oxide and nickel-coated aluminum), was added. The reaction vessel was then sealed and transferred to a constant temperature chamber, kept at 90°C for 3 h, and cooled to room temperature. The resulting aerogel block was then rapidly frozen using liquid nitrogen. The specific operation process involves placing the sample in a cryogenic container and then adding liquid nitrogen for about 1 minute, which quickly freezes the sample into a block. Liquid nitrogen can rapidly cool the sample to -196℃, achieving a quick-freezing effect. The quick-freezing process is to maintain the three-dimensional structure of the graphene hydrogel. The freeze-drying process involves sublimation drying of the ice to obtain a graphene aerogel structure. The sample is then transferred to a freeze dryer, where the freeze-drying temperature is -55 to -60℃ for 72 hours to obtain a nickel-coated aluminum / graphene composite aerogel material.

[0057] The nickel-coated aluminum / graphene composite aerogel material prepared in Example 3 was added to molten paraffin and molded into cylinders and cylindrical rings, which were used for electromagnetic parameter testing and microwave absorption (MA) measurement, respectively.

[0058] Figure 5 The graph shows the reflection loss curves of the nickel-clad aluminum / graphene composite aerogel material prepared in Example 3 at different thicknesses within the frequency range of 0.045–18 GHz. At a frequency of 14.77 GHz, the reflection loss reaches a minimum of -40.0090 dB across the entire frequency band, with a matching thickness of only 2.3 mm and an effective absorption bandwidth of 6.3740 GHz. With a further increase in the nickel-clad aluminum ratio, the reflection loss decreases from -56.1638 dB to -40.0090 dB, and the effective absorption bandwidth widens from 5.5661 GHz to 6.5740 GHz, covering the range of 11.5–18 GHz, and is expected to achieve effective absorption of electromagnetic waves at even higher frequencies. The reduction in reflection loss further highlights the limitations of the nickel-clad aluminum alloy's absorption performance, but the further widening of the effective absorption bandwidth also demonstrates the control of impedance matching performance of graphene-based absorbing materials after the nickel-clad aluminum alloy is combined with graphene oxide, resulting in excellent absorption performance of the nickel-clad aluminum / graphene composite aerogel absorbing material.

[0059] Comparative Example 1

[0060] The difference between Comparative Example 1 and Example 1 is that nickel-coated aluminum alloy is not added in step (2), but the rest of the process is exactly the same.

[0061] The pure graphene aerogel material prepared in Comparative Example 1 was added to molten paraffin and molded into cylinders and cylindrical rings, which were used for electromagnetic parameter testing and microwave absorption (MA) measurement, respectively.

[0062] Figure 2 The graph shows the reflection loss curves of the pure graphene aerogel material prepared for Comparative Example 1 at different thicknesses within the frequency range of 0.045–18 GHz. At a frequency of 9.02 GHz, the reflection loss is the lowest in the entire frequency band, reaching -27.8931 dB. With a matching thickness of 9.5 mm, the effective absorption bandwidth is only 2.3870 GHz. This is because although the three-dimensional structure of the aerogel can improve mass transfer and electron transfer, the impedance matching performance of graphene-based microwave absorbing materials is poor due to their high conductivity and lack of magnetic loss properties. This results in the pure graphene aerogel having relatively low reflection loss and a narrow effective absorption bandwidth, and it cannot achieve effective microwave absorption in the high-frequency band.

[0063] The experimental results from the comparative examples and Example 1 demonstrate the advantages of the technical solution of this application in preparing nickel-clad aluminum / graphene composite aerogel absorbing materials by combining nickel-clad aluminum alloy with graphene oxide.

[0064] Comparative Example 2

[0065] The difference between Comparative Example 2 and Example 1 is that in step (2), nickel-coated aluminum is replaced with pure nickel (average particle size of 50 nm), while the rest of the process is exactly the same.

[0066] The nickel / graphene aerogel material prepared in Comparative Example 2 was added to molten paraffin and molded into cylinders and cylindrical rings, which were used for electromagnetic parameter testing and microwave absorption (MA) measurement, respectively.

[0067] Figure 6 The graph shows the reflection loss curves of the nickel / graphene composite aerogel material prepared in Comparative Example 2 at different thicknesses within the frequency range of 2–18 GHz. Nickel is a ferromagnetic material with high permeability and magnetic loss capability. The nickel / graphene composite aerogel material prepared after being combined with graphene exhibits the lowest reflection loss RL at a low frequency of 5.52 GHz. min It can reach -37.5183dB, but the matching thickness is relatively high and the effective absorption bandwidth (RL<-10dB) is relatively narrow.

[0068] Comparative Example 3

[0069] The difference between Comparative Example 3 and Example 1 is that in step (2), nickel-coated aluminum is replaced with pure aluminum (particle size of 0.1-1000 μm), while the rest of the process is exactly the same.

[0070] The aluminum / graphene aerogel material prepared in Comparative Example 3 was added to molten paraffin and molded into cylinders and cylindrical rings, which were used for electromagnetic parameter testing and microwave absorption (MA) measurement, respectively.

[0071] Figure 7 The image shows the reflection loss curves of the aluminum / graphene composite aerogel material prepared in Comparative Example 3 at different thicknesses within the frequency range of 2–18 GHz. Aluminum powder has a much higher conductivity than graphene oxide. After the two are combined, the aluminum / graphene composite aerogel material has an excessively high complex permittivity and poor impedance matching. The incident electromagnetic waves are largely reflected rather than lost, and it has almost no effective absorption bandwidth (RL < -10 dB).

[0072] Therefore, the results of the embodiments and comparative examples show that the nickel-clad aluminum used in this application combines the characteristics of nickel and aluminum. As a specific alloy structure, nickel-clad aluminum has low density, good conductivity and magnetism, excellent microwave absorption performance, and corrosion resistance. Nickel-clad aluminum combines the magnetic loss of nickel and the electrical loss of aluminum, and also has interfacial polarization loss between the two phases formed by nickel and aluminum. Therefore, nickel-clad aluminum has a wider absorption bandwidth and higher absorption efficiency. In addition, the core-shell structure of nickel-clad aluminum can avoid the oxidation and corrosion of aluminum, thus improving the service life of the microwave absorbing agent. As shown in the comparative examples, elemental nickel and elemental aluminum are not easy to disperse uniformly in graphene oxide solution due to the large difference in density between nickel and aluminum. Mixing them with graphene oxide to prepare aerogels leads to poor synergistic effect among the three. Therefore, the specific alloy structure of nickel-clad aluminum in this application is more conducive to the preparation of microwave absorbing materials.

Claims

1. A nickel-coated aluminum / graphene composite aerogel material, characterized in that: The raw materials for preparing this material include: nickel-coated aluminum and graphene oxide, wherein the mass ratio of nickel-coated aluminum to graphene oxide is 0.06 to 0.18:1, and the nickel-coated aluminum and graphene oxide undergo a reduction reaction with a reducing agent to obtain the final aerogel material; the reducing agent is L-ascorbic acid. The specific preparation steps for nickel-coated aluminum / graphene composite aerogel materials include: (1) Preparation of graphene oxide aqueous dispersion: Weigh graphene oxide powder and add it to deionized water. Mix it ultrasonically at room temperature, adjust the pH of the mixture to neutral, and then mechanically peel it off by a high-speed disperser to obtain the graphene oxide aqueous dispersion. (2) Preparation of nickel-coated aluminum / graphene composite aerogel material: Add nickel-coated aluminum to the aqueous dispersion of graphene oxide prepared in step (1) and sonicate at room temperature to fully disperse the nickel-coated aluminum in the aqueous dispersion of graphene oxide. Then add the reducing agent L-ascorbic acid. Then seal the reaction vessel and transfer it to a constant temperature oven. Keep it at 80-100℃ for 1-5 hours. Then cool it to room temperature and quickly freeze the resulting aerogel block. Then transfer it to a freeze dryer and freeze dry for 24-96 hours to obtain the nickel-coated aluminum / graphene composite aerogel material.

2. The nickel-coated aluminum / graphene composite aerogel material according to claim 1, characterized in that: The graphene oxide has a sheet diameter of 0.4–5 μm and a thickness of 0.5–1.0 nm.

3. The nickel-coated aluminum / graphene composite aerogel material according to claim 1, characterized in that: The nickel-clad aluminum is composed of an aluminum core wrapped with a layer of nickel, with a composition of 60-90 wt% nickel and 10-40 wt% aluminum.

4. The nickel-coated aluminum / graphene composite aerogel material according to claim 3, characterized in that: The nickel-coated aluminum consists of an aluminum core wrapped with a layer of nickel, with a composition of 70-85 wt% nickel and 15-25 wt% aluminum.

5. The nickel-coated aluminum / graphene composite aerogel material according to claim 4, characterized in that: The aqueous dispersion of graphene oxide described in step (1) has a concentration range of 0.01-0.02 g / mL for the graphene oxide powder in the dispersion.

6. The nickel-coated aluminum / graphene composite aerogel material according to claim 5, characterized in that: The temperature of the transfer to the constant temperature chamber in step (2) is 85-95℃ and kept at that temperature for 2.5-3.5 hours.

7. The nickel-coated aluminum / graphene composite aerogel material according to claim 5, characterized in that: The quick-freezing in step (2) is done by using liquid nitrogen. The specific operation process is to place the sample in a low-temperature resistant container and then add liquid nitrogen, and the sample will be quick-frozen into a block. The freeze-drying temperature in step (2) is -55 to -60°C.

Citation Information

Patent Citations

  • Dual network hydrogel-derived graphene / tin-nickel alloy composite material as well as preparation method and application thereof

    CN107528052A

  • Magnetic graphene-based aerogel material with magnetic field and pressure simultaneously-sensing effect and preparation method of magnetic graphene-based aerogel material

    CN109400107A